Extraction and characterization of rice straw cellulose nanofibers by an optimized chemomechanical method. Issue 7 (31st October 2013) - Nasri‐Nasrabadi, Bijan; Behzad, Tayebeh; Bagheri, Rouhollah
Abstract In this study, a chemomechanical method was performed to extract nanofibers from rice straw. This procedure included swelling, acid hydrolysis, alkali treatment, bleaching, and sonication. X‐ray diffractometer was employed to investigate the effect of acid hydrolysis conditions and other chemical treatments on the chemical structure of the extracted cellulose fibers. It was concluded that by increasing the acid concentration and hydrolysis time, the crystallinity of the extracted fibers was increased. The optimum acid hydrolysis conditions were found to be 2M and 2 h for the acid concentration and hydrolysis time, respectively. The chemical compositions of fibers including cellulose, hemicelluloses, lignin, and silica were determined by different examinations. It was noticed that almost all the silica content of fibers was solubilized in the swelling step. Moreover, the achieved results showed that the cellulose content of the alkali treated fibers was increased around 71% compared to the raw materials. ATR‐FTIR was applied out to compare the chemical structure of untreated and bleached fibers. The dimensions and morphology of the chemically and mechanically extracted nanofibers were investigated by scanning electron microscopy, field emission scanning electron microscopy, and transmission electron microscopy. The results of the image analyzer showed that almost 50% of fibers have a diameter within a range of 70–90 nm and length of several micrometers. The thermal gravimetric analyses were performed on the untreated and bleached fibers. It was demonstrated that the degradation temperature was increased around 19% for the purified fibers compared to raw materials. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40063.